Corticosteroid Treatment in Sydenham Chorea: A 27-Year Tertiary Referral Center Experience - Alberto Maria Cappellari; Greta Rogani; Giovanni Filocamo; Antonella Petaccia (MDPI AG, 2023)
Objective: The purpose of this study was to investigate the effectiveness of corticosteroid therapy for children suffering from Sydenham chorea (SC). Methods: The design of the study was observational, retrospective and conducted at the single center of the Rheumatology Unit of Policlinic Hospital of Milan, Italy, from May 1995 to May 2022. All data about the patients were collected from medical records. Results: From a total of 59 patients enrolled in the study (44 females and 15 males; median age 9.3 years, range 7.4-10.6 years), 49 were eligible for primary outcome analysis (10 patients were excluded due to incomplete data). Overall, 75% of patients received steroid therapy, while the remaining cases were treated with symptomatic drugs, including neuroleptics and antiseizure drugs. We found that the duration of chorea was significantly shorter in patients treated with corticosteroids in comparison to those receiving symptomatic treatment (median time: 31 vs. 41 days, p = 0.023). Additionally, patients with arthritis at the onset of the disease had a longer duration of chorea than those without arthritis (median time 90.5 vs. 39 days, p = 0.02). We also found that chorea recurred in 12% of the patients and seemed to be linked to a younger age at onset (p = 0.01). Conclusions: The study suggests that corticosteroid therapy can lead to a faster resolution of SC when compared to neuroleptics and antiseizure drugs treatment.